The role of adenosine in alcohol-induced respiratory suppression. (1st January 2023) - Purnell, Benton S.; Thompson, Sydney; Bowman, Tenise; Bhasin, Jayant; George, Steven; Rust, Brian; Murugan, Madhuvika; Fedele, Denise; Boison, Detlev
Abstract: Alcohol-related poisoning is the foremost cause of death resulting from excessive acute alcohol consumption. Respiratory failure is crucial to the pathophysiology of fatal alcohol poisoning. Alcohol increases accumulation of extracellular adenosine. Adenosine suppresses breathing. The goal of this investigation was to test the hypothesis that adenosine signaling contributes to alcohol-induced respiratory suppression. In the first experiment, the breathing of mice was monitored following an injection of the non-selective adenosine receptor antagonist caffeine (40 mg/kg), alcohol (5 g/kg), or alcohol and caffeine combined. Caffeine reduced alcohol-induced respiratory suppression suggesting that adenosine contributes to the effects of alcohol on breathing. The second experiment utilized the same experimental design, but with the blood brain barrier impermeant non-selective adenosine receptor antagonist 8-sulfophenyltheophylline (8-SPT, 60 mg/kg) instead of caffeine. 8-SPT did not reduce alcohol-induced respiratory suppression suggesting that adenosine is contributing to alcohol-induced respiratory suppression in the central nervous system. The third and fourth experiments used the same experimental design as the first, but with the selective A1 receptor antagonist DPCPX (1 mg/kg) and the selective A2A receptor antagonist istradefylline (3.3 mg/kg). Istradefylline, but not DPCPX, reduced alcohol-induced respiratory suppression indicating an A2A receptor mediated effect. In the fifth experiment, alcohol-induced respiratory suppression was evaluated in Adk +/- mice which have impaired adenosine metabolism. Alcohol-induced respiratory suppression was exacerbated in Adk +/- mice. These findings indicate that adenosinergic signaling contributes to alcohol-induced respiratory suppression. Improving our understanding of how alcohol affects breathing may lead to better treatment strategies and better outcomes for patients with severe alcohol poisoning. Highlights: Non-selective adenosine receptor antagonism reduces respiratory suppression by alcohol. Peripheral adenosine receptor antagonism does not alter respiratory suppression by alcohol. A2A, but not, A1 specific receptor antagonism reduces respiratory suppression by alcohol. Reduction in adenosine metabolism increases respiratory suppression by alcohol. These results suggest that adenosine contributes to respiratory suppression by alcohol.